THE EDUCATIONAL IMPLICATIONS OF A CHILD’S EMOTIONAL JOURNEY IN FACING THE LOSS OF A FATHER FIGURE IN THE NOVEL AYAH, WHERE IS THIS GOING? - Yulyanti, Caci Selfi; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (Kopertis Region IV Jabar and Banten, 2026)
This study aims to describe the emotional journey of children in dealing with the loss of the father figure as represented in the novel Father, This Is the Direction to Where, huh? by Khoirul Trian. This study uses a literary psychology approach with Sigmund Freud's psychoanalytic theory which includes aspects of id, ego, and superego. The research method used is qualitative descriptive with data collection techniques in the form of documentation studies through the extraction of relevant quotes from the novel. The data analysis technique is carried out using content analysis with the stages of reading the text in depth, determining the unit of analysis, classifying the data based on psychological aspects, and interpreting the meaning of the text. The results showed that the id aspect was the most dominant element with six citations, while the ego and superego aspects were found in two citations each. Thus, this novel represents the psychological process of children who experience the loss of a father in a complex and layered manner, as well as depicting psychological dynamics that are relevant to the emotional phenomena of the younger generation in the Indonesian social context.